FLORA AND FAUNA RARE APPLICATIONS IN INDONESIA USING MACROMEDIA FLASH MX 8.0 - Aldila Febrina; Yulina, Skom., MMSI Yulina, Skom., MMSI (Jurnal Sistem Informasi, 2008)
At this writing discusses the application of Flora and Fauna Rare in Indonesia usingMacromedia Flash MX 8.0. This application is made with the aim of providinginformation to the children to be more familiar with rare flora and fauna in Indonesiaand to foster caring attitudes towards flora and fauna are protected in Indonesia. Florais all herbs contained in a sector in a region or period. Fauna are all animals containedin something the area or something. Rare is a rare, rare flora and fauna are scarce inIndonesia is part of a national asset that must be conserved and preserved. Perhapsmany people have not known the Flora and Fauna of the rare and protected by theIndonesian government.